2007
DOI: 10.1089/end.2007.9945
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Kidney: Associated Diseases and Treatment

Abstract: The incidence of pelvic kidney has been approximated at between 1 in 2200 and 1 in 3000. The ectopic kidney is thought to be no more susceptible to disease than the normally positioned kidney, except for the development of calculi and hydronephrosis. Because of the greater risk of injuring aberrant vessels or overlying abdominal viscera and nerves, the pelvic kidney presents special treatment challenges. Alternative approaches to treating nephrolithiasis may yield better outcomes. The tortuous ureter often ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 38 publications
0
86
0
7
Order By: Relevance
“…The incidence of renal ectopia is reported between 1 in 2,200 and 1 in 3,000 [1]. However, a study screening 132,686 school children (6 to 15 years of age) found a lower incidence of 1 in 5000 children [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of renal ectopia is reported between 1 in 2,200 and 1 in 3,000 [1]. However, a study screening 132,686 school children (6 to 15 years of age) found a lower incidence of 1 in 5000 children [4].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of a pelvic kidney is estimated between 1 in 2,200 and 1 in 3,000 [1]. Given the rarity of a pelvic kidney, it is often an incidental finding on imaging studies or an unsuspected finding in patients presenting with vague or atypical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Increased incidence of renal cell tumors in pelvic kidneys should be taken into consideration (14) . For that reason nephrectomy has been recommended for pelvic and nonfunctional kidneys (15) .…”
Section: Discussionmentioning
confidence: 99%
“…During ascent, the kidneys proceed through a bifurcation formed by the umbilical arteries. If one of the kidneys fails to pass this point, it remains within the pelvis next to the common iliac artery (Sadler 1990;Cocheteux et al 2001;Cinman et al 2007). …”
Section: Embryology Of Renal Ectopiamentioning
confidence: 99%